Efektivitas Penggunaan Laboratorium High Voltage di Politeknik Ilmu Pelayaran (PIP) Semarang - Andy Wahyu Hermanto; M. Imroni Mubin; Achmad Ridwan (Politeknik Ilmu Pelayaran Semarang, 2021)
Semarang Merchant Marine Polytechnic (PIP Semarang) is a university that provides vocational education in the field of shipping. The high voltage laboratory is a means of supporting the practice of electrical equipment on board a ship based on a high voltage of 6.6 Kv. Based on the results of the researchers' preliminary observations and observations, it is known that the use of the high voltage laboratory during the 2019 school year is very minimal, namely 25.5 hours for 1 year. The purpose of this study is to see the use of the high voltage laboratory at PIP Semarang, what security is used in the use of the high voltage laboratory at PIP Semarang, and the efforts made to overcome the problems used in the use of the high voltage laboratory at PIP Semarang. The research method used in this research is a qualitative method. Data obtained from the results of distributing questionnaires to cadets. In addition, interviews were also conducted with Engineering Study Program lecturers. Secondary data obtained from literature study, observation and documentation. Based on the results of data analysis, it can be denied that the use of the high voltage laboratory at PIP Semarang is still not optimal and effective. This can be proven by the results of the questionnaire recapitulation showing that the use of the high voltage laboratory is 32% very effective, 4% effective, 60% less effective, and 4% ineffective.